The Identities of Young America: A Case of American Exceptionalism and Emerging Identities in Letters from an American Farmer - Daryaee Motlagh, Ebrahim (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2021)
This article is an attempt to examine the emerging identities and the primary examples of exceptionalism in early American literature by a review of excerpts from the